Kepuasan Pasien Peserta Program Jaminan Kesehatan Nasional terhadap Pelayanan Kefarmasian di Apotek - Yuniar, Yuyun; Handayani, Rini Sasanti (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Pharmacy is a place where a pharmacist provides pharmaceutical services. To improve services, it is necessary to carry out an evaluation of patients’s or consumers’ satisfaction on pharmaceutical services.This research aimed to assess the satisfaction of the patients covered by national health insurance programme (JKN) and to find out the relationship of patients’ characteristics and their satisfaction. This research used a cross sectional survey design, conducted for patients visiting pharmacy to redeem the prescribed drug in Tangerang Selatan city, Serang district, Bekasi city, Bogor district, Yogyakarta city, Bantul district, Solo city, and Sragen district. The sample was 152 adult JKN patients chosen by accidental sampling. Data were collected using self assessment questionnaire analyzed using chi square analysis. This study found that the highest level of dimension of pharmaceutical services satisfaction was empathy and the lowest one was assurance, in term of the availability of drugs and the number of drugs that was covered by JKN scheme. Among 5 characteristics (i.e: age, sex, marriage status, education, and occupation), only occupation variable that had significant correlation with satisfaction. The pharmacy management should communicate with the JKN provider regarding the kinds of drugs covered and concern with the drugs availability in the pharmacy.